PENGARUH METODE PEMBELAJARAN KOLABORATIF TERHADAP PRESTASI BELAJAR MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN SISWA KELAS XI SMK SL MAS’UDIYAH SRESEH SAMPANG - Hilyatun Nisa; Asri Bariqoh; Sahrul Muzekki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2025)
This study aims to determine the effectiveness and influence of collaborative learning methods on the learning achievements of Grade XI students in Civic Education at SMK Al Mas'udiyah Sreseh Sampang. The method used in this study is quantitative with an experimental research design. The population is all Grade XI students at SMK Al Mas'udiyah Sreseh Sampang. The sample was selected using purposive sampling. Data collection methods included tests, observation, and documentation. Data analysis was performed using t-tests, which had previously been determined to be homogeneous and normal. The results of this study show that: 1) The level of effectiveness of the collaborative learning method applied to Civic Education in the 11th grade at SMK Al Mas'udiyah is in the category of quite effective. This can be seen from the N-Gain Score result of 59.3% (fairly effective category) and from the results of observations of student activities conducted during 3 meetings, which obtained a percentage of 93.3% (fairly effective) because it met the criteria of ≥ 75%. 2) The effect of collaborative learning methods on the learning achievement of Civics subject students in class XI at SMK Al Mas'udiyah Sreseh Sampang. This is shown by the results of hypothesis testing conducted using a t-test with a significance level of 0.05, which yielded a t-count > t-table, namely 7.074 > 2.021. Thus, it can be seen that there was an increase in the average post-test score of the experimental class, which was 87.09, and the control class, which was 77.55.